Dimensionality of the Wisconsin Schizotypy Scales-Brief Forms in College Students. (11th November 2013) - Fonseca-Pedrero, Eduardo; Paino, Mercedes; Ortuño-Sierra, Javier; Lemos-Giráldez, Serafín; Muñiz, José
Abstract : Wisconsin Schizotypy Scales are one of the most used measuring instruments for the assessment of psychometric risk for psychosis. The main goal of the present study was to analyze the internal structure of the Wisconsin Schizotypy Scales-Brief (WSS-B) forms and the reliability of the scores in a large sample of college students. The final sample was comprised by a total of 1349 students, 288 males, with a mean age of 20.48 years (SD = 2.58). The results indicated that the WSS-B scores presented adequate psychometric properties. Cronbach's alfa coefficient for total scores in WSS-B ranged from 0.86 to 0.93. Analysis of the internal structure of the WSS-B, through confirmatory factor analysis and exploratory structural equation modeling, yielded a four factor solution (Magical Ideation, Perceptual Aberration, Social Anhedonia, and Physical Anhedonia) as the most adequate. Statistically significant differences in mean scores of WSS-B by sex were found. These results provided new validity evidence of the WSS-B scores in an independent sample of nonclinical young adults. The WSS-B seems to be useful, brief, and easy to administrate for the screening of extended psychosis phenotype in the general population.